Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a = \(\frac{x\left(x-2\right)}{x^2+8x-20}=\frac{x\left(x-2\right)}{\left(x-2\right)\left(x+10\right)}\)
th1 : x > 2
=> X> 2
=> a = \(\frac{x\left(x-2\right)}{\left(x-2\right)\left(x+10\right)}\frac{x}{x+10}\)
th2 : X < 2
a = \(\frac{-x\left(x-2\right)}{\left(x-2\right)\left(x+10\right)}\frac{x}{x+10}\)
Ta có:\(\frac{\left[x\left(x-2\right)\right]}{x^2+8x-20}+12x-3=\frac{x\left(x-2\right)}{x^2-2x+10x-20}+12x-3\)
\(=\frac{x\left(x-2\right)}{x\left(x-2\right)+10\left(x-2\right)}+12x-3=\frac{x\left(x-2\right)}{\left(x+10\right)\left(x-2\right)}+12x-3\)
\(=\frac{x}{x+10}+12x-3=\frac{x+\left(12x-3\right).\left(x+10\right)}{x+10}=\frac{x+12x^2+120x-3x-30}{x+10}\)
\(=\frac{12x^2+118x-30}{x+10}\)
a) P(x)=8x6-4x2+5x5-12x+7x2-2x5
=8x6+(-4x2+7x2)+(5x5-2x5)-12x
=8x6+3x2+3x5-12x
b) P(x)=8x6+3x2+3x5-12x
=8x6+3x5+3x2-12x
P(x)-Q(x)=(8x6+3x5+3x2-12x)-(2x5-6x2+8x-2x6)
=8x6+3x5+3x2-12x-2x5+6x2-8x+2x6
=(8x6+2x6)+(3x5-2x5)+(3x2+6x2)+(-12x-8x)
=10x6+x5+9x2-20x
R(x)-Q(x)=4x6-8x2
R(x) =(4x6-8x2)+Q(x)
R(x) =(4x6-8x2)+(2x5-6x2+8x-2x6)
R(x) =4x6-8x2+2x5-6x2+8x-2x6
R(x) =(4x6-2x6)+(-8x2-6x2)+2x5+8x
R(x) =2x6-14x2+2x5+8x
\(B=x^{15}-8x^{14}+8x^{13}-8x^{12}+...+8x-5\)
\(=x^{15}-\left(x+1\right)x^{14}+\left(x+1\right)x^{13}-\left(x+1\right)x^{12}+...+\left(x+1\right)x-x+2\)
\(=x^{15}-x^{15}-x^{14}+x^{14}+x^{13}-x^{13}-x^{12}+...+x^2+x-x+2\)
\(=2\)